Detached Eddy Simulation of Complex Separation Flows over a Modern Fighter Model at High Angle of Attack (Communications in Computational Physics, 2017)
This paper presents the simulation of complex separation flows over a modernfighter model at high angle of attack by using an unstructured/hybrid grid basedDetached Eddy Simulation (DES) solver with an adaptive dissipation second-orderhybrid scheme. Simulation results, including the complex vortex structures, as well asvortex breakdown phenomenon and the overall aerodynamic performance, are analyzedand compared with experimental data and unsteady Reynolds-Averaged Navier-Stokes(URANS) results, which indicates that with the DES solver, clearer vortical flowstructures are captured and more accurate aerodynamic coefficients are obtained. Theunsteady properties of DES flow field are investigated in detail by correlation coefficient analysis, power spectral density (PSD) analysis and proper orthogonal decomposition(POD) analysis, which indicates that the spiral motion of the primary vortex onthe leeward side of the aircraft model is highly nonlinear and dominates the flow field.Through the comparisons of flow topology and pressure distributions with URANSresults, the reason why higher and more accurate lift can be obtained by DES is discussed.Overall, these results show the potential capability of present DES solver inindustrial applications.